The Impact of Teachers’ Qualifications on Classroom Performance: A Comparative Analysis - Adhikari, Ram Prasad; Nepal, Bijaya; Manandhar, Dev Chandra; Bhandari, Ram Bahadur; Dahal, Bidhya; Dhakal, Dipendra; Manandhar, Nita (A Peer Reviewed Journal on Social Sciences, 2024)
This study examines the relationship between teachers' qualifications and their performance in the classroom, focusing on how various dimensions of teacher competence; academic achievement, professional development, certification, and teaching experience impact educational outcomes. The research integrates findings from multiple studies to identify how these factors influence teacher effectiveness and student achievement. The total population of study were 93 senior community schools in Makawanpur District. The study employed a quantitative research design with cross-sectional data collection, surveying 66 teachers from 14 senior community schools in Makawanpur district, Nepal. The analysis included survey data, semi-structured interviews with teachers, students, and administrators, and student performance records 2023. Multiple regression tests for R-square value that reveal that impact of teachers' qualifications, including educational degrees, additional certifications, and teaching experience, significantly impacted their effectiveness in instructional strategies, planning and preparation, classroom-environment, behaviour management, student engagement, communication, and reflection on professional development. Key findings indicate that academic degrees and professional development training played crucial roles in enhancing teacher performance, while teaching experience and additional certifications also contributed significantly. The results suggest that while professional development and additional certifications are beneficial, their impact may be less significant compared to academic qualifications. The study highlights the need for comprehensive policies to improve teacher qualifications, enhance professional development opportunities, and ensure effective certification processes to elevate overall educational quality. This research provides valuable insights for policymakers, educational leaders, and practitioners aiming to improve educational outcomes through better understanding and support of teacher competencies. Future research should explore the contextual factors influencing these relationships and examine strategies to optimize teacher training and certification processes.